Coulomb Planar Periodic Motion of n Equal Charges in the Field of n Equal Positive Charges Fixed at a Line and Constant Magnetic Field - W. I. Skrypnik (Advances in Mathematical Physics)
We consider a neutral Coulomb planar system of n equal negative charges in a constant magnetic field and a field of n equal fixed positive charges and construct a periodic solution of the equation of motion such that each negative charge is close to its own positive fixed charge.